(untitled) (World Economics and Finance Bulletin, 2025)
This article explores the transformation of Corporate Social Responsibility (CSR) in the face of contemporary global challenges, including the pandemic, climate crisis, digitalization, and geopolitical instability. It reviews international experiences in adapting CSR to these new conditions, with a particular focus on integrating Environmental, Social, and Governance (ESG) principles into strategic management. The study demonstrates that leading global corporations are shifting from mere declarations to tangible, measurable tools for CSR implementation. These include ESG reporting, carbon audits, digital monitoring platforms, and participation in carbon markets. The article also highlights the growing adoption of sustainable reporting practices, increased stakeholder engagement, and the rise of ESG-focused asset management. Key risks are identified, ranging from “greenwashing” to institutional barriers, alongside strategies for mitigating these challenges. The conclusion emphasizes the need for a comprehensive, systemic approach to CSR as a core element of sustainable business development at the global level